2017
DOI: 10.4178/epih.e2017052
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare worker infected with Middle East Respiratory Syndrome during cardiopulmonary resuscitation in Korea, 2015

Abstract: OBJECTIVESDuring the outbreak of the Middle East Respiratory Syndrome (MERS) in Korea in 2015, the Korea Centers for Disease Control and Prevention (KCDC) confirmed a case of MERS in a healthcare worker in Daejeon, South Korea. To verify the precise route of infection for the case, we conducted an in-depth epidemiological investigation in cooperation with the KCDC.METHODSWe reviewed the MERS outbreak investigation report of the KCDC, and interviewed the healthcare worker who had recovered from MERS. Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 14 publications
0
37
0
8
Order By: Relevance
“…One retrospective cohort study has reported that one of nine HCWs who participated in cardiac compression developed severe acute respiratory syndrome (SARS) [25]. Of the six HCWs who performed CPR on a patient with MERS, one acquired the infection [11]. Experiences from the outbreaks of highly contagious diseases, such as SARS and MERS, taught us that HCWs should be protected from airborne disease transmission when performing CPR [11,12,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One retrospective cohort study has reported that one of nine HCWs who participated in cardiac compression developed severe acute respiratory syndrome (SARS) [25]. Of the six HCWs who performed CPR on a patient with MERS, one acquired the infection [11]. Experiences from the outbreaks of highly contagious diseases, such as SARS and MERS, taught us that HCWs should be protected from airborne disease transmission when performing CPR [11,12,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Of the six HCWs who performed CPR on a patient with MERS, one acquired the infection [11]. Experiences from the outbreaks of highly contagious diseases, such as SARS and MERS, taught us that HCWs should be protected from airborne disease transmission when performing CPR [11,12,26,27]. The current international CPR guidelines do not address the extent of airway protection required by HCWs when performing CPR on patients with suspected or confirmed airborne diseases [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eine erste systematische Übersichtsarbeit und Metaanalyse von Studien über das Risiko der SARS-Übertragung durch AGPs wurde 2011 vonTran et al vorgelegt [14]. Darin werteten die Autoren je 5 klinische Fall-Kontroll-und retrospektive Kohortenstudien vongemessen an den GRADE-Kriterien[13] sehr geringer Qualität aus und fanden signifikant erhöhte Infektionsrisiken nur für folgende AGPs: ▪ Intubation (8 Studien, Gesamt Odds Ratio, OR 6,6) Übertragung von MERS auf eine Krankenpflegerin im Rahmen einer Reanimation berichtet[16,17]. Der Bericht lässt allerdings offen, ob die Übertragung tatsächlich durch Aerosole erfolgte oder auf anderen Wegen, z.…”
unclassified